Fundamental issues related to cooperation of rescue entities - Bogdan Kogut; Jan Ziobro (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The study presents the subject matter of joint ventures of rescue entities on the example of the State Fire Service and the National Emergency and Fire System. The study defines the term ‘public safety’ which is understood as living in such an environment in which citizens do not feel threat to their existence or to their basic life interests. The responsibility of the state is to provide formal, institutional and practical guarantees of protection within the socially acceptable levels of risk. On this basis, the paper presents the scope of cooperation of the above entities, analyzes applied solutions related to the organization of this cooperation and evaluates their efficiency.